Water Quality of River Kosi and Rajera System at Rampur (India): Impact Assessment - Ashish Kumar; Yogendra Bahadur (Journal of Chemistry)
River Kosi, an important tributary of river Ramganga, is one of the important rivers of Uttaranchal and Uttar Pradesh After traveling for about 100 kms in lower Himalayas with higher velocity, it emerges at Ramnagar in Indo-Gangetic plains. Here, the major portion of city sewage is discharged into it. Then, it flows through the famous rice belt area of Kashipur, where a number of polluting industries discharge their highly polluted effluents into it. To determine the extent of pollution in downstream district Rampur, a study was conducted. The aim of this study was to evaluate the effect of dilution caused by the merger of river Rajera with Kosi River. For this samples, were collected from three stations and analyzed for various parameters for the period of one year. The study revealed higher levels of industrial pollution as compared to domestic pollution. It also shows the alleviating effects of dilution caused by the merger of river Rajera.